Dataset Associated with the Research Article Titled: Webs of Science: Developmental Networks Influence Women’s Integration into STEM Fields - Hernandez, Paul R.; Patterson, Megan S.; Nyanamba, Juliet M.; Adams, Amanda S.; Barnes, Rebecca T.; Burt, Melissa; Clinton, Sandra M.; Pollack, Ilana B.; Fischer, Emily V. (Colorado State University. Libraries, 2021)
Mentorship can be part of the solution to developing a more diverse global scientific workforce, but robust longitudinal evidence is limited. Developmental mentor network theory can advance our understanding of the impact of a wide range of mentors across social contexts by distinguishing between the content of mentorship support (eg career support) and the structural characteristics of an individual’s mentor network (eg density of connections among mentors). We tested the influence of mentor network characteristics on longitudinal social integration into earth and environmental sciences, as indicated by science identity development (a key indicator of social integration) and STEM graduate school applications, in a sample of 233 undergraduate women at 9 universities in the U.S. Findings indicate that belonging to close-knit, larger, and skill-focused mentorship networks creates a “sticky web” of social connections, providing information and resources that increase retention of college women in the earth and environmental sciences.
Department of Teaching, Learning, and Culture, Texas A&M University.
Department of Health and Kinesiology, Texas A&M University.
Department of Educational Psychology, Texas A&M University.
Department of Geography & Earth Sciences, UNC Charlotte.
Keywords: developmental network; mentor; gender; STEM education; identity; persistence